Improvement in Work Ability, Psychological Distress and Pain Sites in Relation to Low Back Pain Prognosis: A Longitudinal Observational Study in Primary Care. Issue 7 (1st April 2019) - Nordstoga, Anne L.; Vasseljen, Ottar; Meisingset, Ingebrigt; Nilsen, Tom I. L.; Unsgaard-Tøndel, Monica
Abstract : Study Design: Prospective observational study pooled from two clinical cohorts. Objective: To investigate the longitudinal relation between multisite pain, psychological distress, and work ability with disability, pain, and quality of life. Summary of Background Data: Knowledge of prognostic factors is essential for better management of patients with low back pain (LBP). All domains of the biopsychosocial model have shown prognostic value; however, clinical studies rarely incorporate all domains when studying treatment outcome for patients with LBP. Methods: A total of 165 patients with nonspecific LBP seeking primary care physiotherapy were included. Mixed-effects models were used to estimate longitudinal relations between the exposure variables and concurrent measures of outcomes at baseline and 3 months. Logistic regression was used to estimate odds ratios for minimal important difference in outcome. Results: Higher work ability was associated with less disability −2.6 (95% confidence interval [CI]: −3.3, −2.0), less pain: −0.4 (95% CI: −0.5, −0.3), and higher quality of life 0.03 (95% CI: 0.02, 0.04). Higher psychological distress and number of pain sites were associated with higher disability: 10.9 (95% CI: 7.7, 14.1) and 2.3 (95% CI: 1.4, 3.2) higher pain: 1.9 (95% CI: 1.3, 2.5) and 0.4 (95% CI: 0.2, 0.5), and lower quality of life: −0.1 (95% CI: −0.2, −0.1) and −0.02 (95% CI: −0.03, −0.01), respectively. Improvement in work ability showed consistent associations with successful outcome for disability (odds ratio [OR]: 4.8, 95% CI: 1.3, 18.1), pain (OR: 3.6, 95% CI: 1.1, 12.1), and quality of life (OR: 4.5, 95% CI: 1.4, 15.1) at 3 months. Reduced psychological distress was associated with improvement in pain only (OR 4.0, 95% CI: 1.3, 12.3). Conclusion: More pain sites, higher psychological distress, or lower work ability showed higher disability, more pain, and lower quality of life in patients with LBP. Only improvement in work ability was consistently related to successful outcomes. Level of Evidence: 2 Abstract : A prospective study investigating the longitudinal relation between multisite pain, psychological distress, and workability in patients with low back pain. Only improvement in work ability was consistently related to successful outcome in disability, pain, and quality of life at 3 months.